Evaluation of the Effect of Patient–Initiated Antiviral Therapy on the Frequency of the Recurrent Herpes Simplex Viral Infection: A Single Center, Retrospective Study - Sugai J; Takeshita T (Clinical, Cosmetic and Investigational Dermatology)
Junichi Sugai,1 Tomoyoshi Takeshita2 1Sugai Dermatology Park Side Clinic, Tochigi, Japan; 2Medical Affairs Department, Maruho Co., Ltd., Osaka, JapanCorrespondence: Tomoyoshi Takeshita, Medical Affairs Department, Maruho Co. Ltd., Osaka, Japan, Tel +81 663 718 913, Fax +81 663 718 927, Email takeshita_emk@mii.maruho.co.jpPurpose: Although recurrent herpes simplex (RHS) is usually self–limiting, it can significantly impair quality of life due to frequent recurrences and associated symptoms. Patient–initiated therapy (PIT) enables patients with RHS to initiate high–dose antiviral medication at their own discretion as soon as prodromal symptoms appear. While famciclovir–based PIT offers the convenience of a single–day treatment and has shown efficacy comparable to low–dose, long–term regimens such as 5–day treatment, no reports have evaluated its impact on the annual recurrence rate. To investigate this further, we conducted a single–center, chart–based retrospective study to assess the effect of PIT on annual recurrence rate.Patients and Methods: Patients who visited a medical institution for RHS and who had their recurrence frequency recorded over the preceding year were included. Annual recurrence number, adherence, treatment efficacy, and other relevant factors were assessed through interviews and questionnaires. The effectiveness and safety of PIT were compared with conventional 5–day oral anti–herpesvirus treatment.Results: Sixty patients who were prescribed famciclovir for PIT were enrolled, of whom 43 with recurrent episodes were included in the efficacy analysis population. The mean number of recurrences during the first year of PIT was 2.8 (SD: 2.1), representing a significant reduction compared to 5.3 (SD: 2.9) during 5–day treatment (p < 0.001). Patient questionnaires indicated high adherence, treatment efficacy, and preference for PIT. Regarding safety, no increase in adverse events was observed compared to 5–day treatment.Conclusion: Famciclovir–based PIT significantly reduced the recurrence rate of RHS, demonstrated high adherence and treatment efficacy, was preferred by patients, and was well tolerated. These results support PIT as a promising therapeutic approach for management of recurrent herpes simplex.Keywords: herpes simplex virus, recurrence rate, patient–initiated treatment, 5–day treatment, famciclovir, real–world clinical practice